Fundamental accounting principles - Wild, John J. (McGraw-Hill, 2007)
With 50 years of success in the principles of accounting market, Fundamental Accounting Principles, 18e by Wild, Larson and Chiappetta has endured and adapted to changes in accounting, technology, and student learning styles. Its innovation is reflected in its extensive use of small business examples, the integration of new computerized learning tools, superior end-of-chapter material, and a highly engaging, pedagogical design. Inclusion of Homework Manager, Homework Mananger Plus and Carol Yacht's General Ledger and Peachtree application software provides students every advantage as they strive to understand the key concepts of accounting and their role in business